1997
DOI: 10.1046/j.1469-8137.1997.00862.x
|View full text |Cite
|
Sign up to set email alerts
|

Laser ablation of the cell wall and localized patch clamping of the plasma membrane in the filamentous fungus Aspergillus: characterization of an anion‐selective efflux channel

Abstract: summary We have used a pulsed u.v. laser to ablate the cell wall of the filamentous fungus Aspergillus niger van Tiegh., and expose the plasma membrane at defined points along the hypha. Using the patch clamp technique, giga ohm seals (up to 20 GΩ) and recordings of plasma membrane ion channels were obtained. We describe, for the first time in fungi, a 43 pS plasma membrane anion efflux channel. Its potential role in cell signalling and pH homeostasis is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…The difficulty in applying the PCT to filamentous fungi (see the introduction) has resulted in a relative dearth of knowledge regarding the electrophysiological properties of ion channels in fungi and their role in hyphal growth. Although the laserassisted PCT allowed the first detailed recordings of ion channels in fungal hyphal cells (30), this technique has resulted in only one other publication (38). Therefore, the ability to clone and functionally express Neurospora ion channels in yeast cells provides an alternative (and possibly a more amenable) approach to the electrophysiological study of ion transporters in filamentous fungi, which should significantly aid the investigation of ion channel function in fungal physiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulty in applying the PCT to filamentous fungi (see the introduction) has resulted in a relative dearth of knowledge regarding the electrophysiological properties of ion channels in fungi and their role in hyphal growth. Although the laserassisted PCT allowed the first detailed recordings of ion channels in fungal hyphal cells (30), this technique has resulted in only one other publication (38). Therefore, the ability to clone and functionally express Neurospora ion channels in yeast cells provides an alternative (and possibly a more amenable) approach to the electrophysiological study of ion transporters in filamentous fungi, which should significantly aid the investigation of ion channel function in fungal physiology.…”
Section: Discussionmentioning
confidence: 99%
“…This allowed, for the first time, a more rigorous identification of several types of plasma membrane ion channel from filamentous fungi. In Aspergillus spp., Roberts et al (30) identified anion efflux and a K ϩ efflux channel (unpublished data) whereas Véry and Davies (38) identified K ϩ and Ca 2ϩ uptake channels in Neurospora crassa. However, despite the successes achieved with the laser ablation PCT on filamentous fungi, progress has been slow.…”
mentioning
confidence: 99%
“…However, highly collimated light sources, such as lasers, can exert a focused radiation pressure that is substantial enough to manipulate large particles, including microbial cells (129). As a result, optical forces can be used to trap, move, pull, twist, or cut individual cells (77,137,159,192,245). Optical manipulation may also be used to measure forces exerted by a microorganism on its environment.…”
Section: Micromanipulationmentioning
confidence: 99%
“…Because the dielectric properties of a cell are responsive to mechanical or chemical perturbation, methods for dielectric spectroscopy such as electrorotation can yield information on both the integrity and the physicochemical properties of individual cells (63). Compared to other methods for investigating the electrical properties of cells (e.g., the use of microelectrodes or patch clamping), electrorotation is relatively noninvasive and does not require extensive cell preparations (106,192,258). Applications for electrorotation include monitoring the effects of antibiotics on single yeast cells (106) and distinguishing between nonviable and viable protozoan cysts on the basis of the direction of their rotation at specific field frequencies (63).…”
Section: Vol 68 2004 Single-cell Microbiology 549mentioning
confidence: 99%
See 1 more Smart Citation